2011
DOI: 10.1371/journal.pone.0025455
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and 17β-Estradiol Promote Arrhythmia in the Female Heart via Alteration of Calcium Handling

Abstract: BackgroundThere is wide-spread human exposure to bisphenol A (BPA), a ubiquitous estrogenic endocrine disruptor that has been implicated as having potentially harmful effects on human heart health. Higher urine BPA concentrations have been shown to be associated with cardiovascular diseases in humans. However, neither the nature nor the mechanism(s) of BPA action on the heart are understood.Methodology/Principal FindingsThe rapid (<7 min) effects of BPA and 17β-estradiol (E2) in the heart and ventricular myocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 41 publications
7
153
3
Order By: Relevance
“…However, the effect of BPA on the heart, an estrogen-sensitive system, remained unknown until recently. We have demonstrated that exposure to nanomolar BPA and/or E 2 rapidly induced arrhythmogenic triggered activities and promoted the development of ventricular arrhythmias in female rat hearts (11). The proarrhythmic effect of BPA was more pronounced in the presence of physiological concentrations of E 2 and was augmented by ␤-adrenergic stress.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…However, the effect of BPA on the heart, an estrogen-sensitive system, remained unknown until recently. We have demonstrated that exposure to nanomolar BPA and/or E 2 rapidly induced arrhythmogenic triggered activities and promoted the development of ventricular arrhythmias in female rat hearts (11). The proarrhythmic effect of BPA was more pronounced in the presence of physiological concentrations of E 2 and was augmented by ␤-adrenergic stress.…”
mentioning
confidence: 85%
“…Gonadectomy surgery was performed by the vendor, and gonadectomized rats were received from the vendor and used 2 wk after surgery. Animals were housed as previously described (11). Sani-chip bedding (Irradiated Aspen Sani-chip; P.J.…”
Section: Animalsmentioning
confidence: 99%
“…[60][61][62] Overall, these in vitro studies have examined a large number of cell types and biological endpoints that may be relevant to cellular function in vivo. The low dose cut-off of 1 × 10 -7 M has been debated and it may be reasonable to shift the low dose cut-off for in vitro studies to 10 One final study deserves attention due to its use of Organization for Economic Cooperation and Development (OECD) guidelines to test the effects of BPA on histopathological changes in the ovary.…”
Section: -53mentioning
confidence: 99%
“…The potential endocrine disrupting effects of BPA was first recognized in 1997 (refs 15-17). Thereafter, several studies also provided evidence on the endocrine disrupting action of BPA [18][19][20][21][22][23][24][25][26][27][28] . BPA is similar in function to the natural hormone 17-estradiol and binds mainly to the estrogen receptor (ER) to exhibit estrogenic activities 29,30 .…”
Section: History Of Bpamentioning
confidence: 99%